Pasolini und die italienische Krise: Eine Arbeitshypothese - Kammerer, Peter (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1995)
Pasolini expressed his views on all questions of social and political changes in Italy from 1943 to1975. Thereby, he anticipated a Jot of today’s problems. His heretical approaches can beuseful for analysing the contemporary crises and a new beginning of the Left.